Effect of D-fructose on the in-vitro corrosion behavior of AZ31 magnesium alloy in simulated body fluid. (10th March 2021) - Pokharel, Durga Bhakta; Liping, Wu; Dong, Junhua; Wei, Xin; Etim, Ini-Ibehe Nabuk; Subedi, Dhruba Babu; Umoh, Aniefiok Joseph; Ke, Wei
Abstract: The effect of adding d -fructose to simulated body fluid (SBF) on the corrosion behavior of AZ31 magnesium (Mg) alloy at 37 °C and at a pH of 7.4 was studied by potentiodynamic polarization (PDP), electrochemical impedance spectroscopy (EIS), potentiostatic polarization and hydrogen (H2 ) collecting techniques, Raman spectroscopy technique, scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy analysis (XPS) and Fourier transformed infrared (FTIR). The results demonstrated that the addition of fructose enhanced the deposition of phosphates forming thick and compact corrosion products, which inhibited the transmission of aggressive ions into the Mg substrate. As a result, both the anodic dissolution of Mg and negative difference effect (NDE) were suppressed. Thus, the corrosion resistance of AZ31 Mg alloy in SBF was significantly improved.